THE RISK ASSESSMENT OF TOXIC DEFEAT OF THE PEOPLE IN THE ACCIDENTAL EMISSION OF HAZARDOUS CHEMICAL SUBSTANCES - Gunko, O. Yu. (Science and Transport Progress, 2008)
The 3D numerical model to simulate the toxicant propagation at an industrial site after the emergency blow-out was developed. The model is based on the transport gradient model and the model of inviscous incompressible fluid. The results of numerical experiments are presented.